Adjustment of progesterone administration after endometrial transcriptomic analysis does not improve reproductive outcomes in women with adenomyosis. Issue 1 (January 2023) - Juárez-Barber, Elena; Cozzolino, Mauro; Corachán, Ana; Alecsandru, Diana; Pellicer, Nuria; Pellicer, Antonio; Ferrero, Hortensia
Highlights: Patients with adenomyosis present a non-receptive endometrial transcriptome. Progesterone adjustment does not improve IVF outcomes in women with adenomyosis. Other molecular mechanisms beyond progesterone regulation affect receptivity. Abstract: Research question: Do patients with adenomyosis present a dysregulated endometrial receptivity that can be reversed with personalized embryo transfer (PET) by transcriptomic-based progesterone adjustment, improving IVF outcomes? Design: A multicentre, retrospective, cohort study that transcriptomically analysed the endometrial receptivity of the endometrium in patients with adenomyosis ( n  = 81) and healthy women ( n  = 231). Subsequently, implantation, biochemical and clinical miscarriage, and live birth rates between adenomyosis patients with one previous implantation failure using donor oocytes who received (n = 59) or did not receive ( n  = 66) PET based on endometrial receptivity, were observed to evaluate if adjusted progesterone improves reproductive outcomes of adenomyosis patients. Results: Patients with adenomyosis significantly presented an altered endometrial receptivity (non-receptive) compared with healthy patients (53.1% versus 37.2%, P  = 0.0179), elevating the risk of adenomyosis patients having a non-receptive endometrium 42.59% higher (95% CI 41.50 to 44.45). No significant differences were found in implantation (62.7% versus 78.8%, P  = 0.0514), biochemical (13.5% versus 3.9%, P  = 0.1223) and clinical (10.8% versus 15.4%, P  = 0.7543) miscarriage, or live birth rates (75.7% versus 80.8%, P  = 0.6066), in patients with PET compared with those without PET. Conclusions: Women with adenomyosis presented an altered expression of genes involved in decidualization, and a higher rate of non-receptive endometrial statuses than controls. Although progesterone is indispensable for implantation, adjusting progesterone before PET, using endometrial transcriptomic signatures, does not improve IVF outcomes in patients with adenomyosis. Other molecular mechanisms beyond progesterone regulation may be involved in implantation failure.